The effect of autonomous learning process on learner autonomy of English public speaking students - Boonma, Nida; Swatevacharkul, Rosukhon (Universitas Pendidikan Indonesia, 2020)
The objectives of this study were to examine the effect of the autonomous learning process (ALP) on learner autonomy of undergraduate students in English public speaking class and its effect size; andÂ to explore how learner autonomy is revealed through the ALP. This study employed a variant of a mixed-methods approach, which is an embedded experimental design. Employing the cluster sampling method, nineteen Thai students were included. The students were trained in the ALP based on the four dimensions of learner autonomy (technical, psychological, political-critical, and sociocultural.) Quantitative data were collected from the Learner Autonomy for Public Speaking (LAPS) questionnaires and analyzed by the dependent samples t-test. Qualitative data were drawn from the Overall Written Reflections, and thematic content analysis was used to analyze the data. The findings revealed that the level of studentsâ€™ learner autonomy in the post-questionnaire significantly increased from the pre-questionnaire (p = 0.00). Its effect size is large (d = 1.28), and learner autonomy, as revealed through the ALP, can be classified into five emerging themes. The themes are (1) use and plans of the learning strategies, (2) evaluation of learning and learning strategies, (3) capacity to provide and accept praise and criticism, (4) increased positive emotions and (5) sense of awareness and a better understanding of self. Recommendations for further study are provided.